Beer-derived nitrogen, phosphorus co-doped carbon quantum dots: Highly selective on–off-on fluorescent probes for the detection of ascorbic acid in fruits. (30th May 2023) - Li, Xinyue; Wang, Chao; Li, Peng; Sun, Xinyang; Shao, Zhiying; Xia, Ji; Liu, Qin; Shen, Fei; Fang, Yong
Graphical abstract: Highlights: Beer was used as a synthetic precursor of biomass carbon quantum dots. Based on "on–off–on", N, P-CQDs can detect Fe 3+ and ascorbic acid in fruits. The N, P-CQDs@Fe 3+ system had a sufficient sensitivity and selectivity. The cytotoxicity of N, P CQDs was low. Abstract: A rapid, facile and ultrasensitive fluorescence sensing system based on beer-derived nitrogen, phosphorus co-doped carbon quantum dots (N, P-CQDs) for the detection of ascorbic acid (AA) in fruits was proposed. N, P-CQDs were successfully synthesized by one-step hydrothermal method, which afforded a high quantum yield (21.7 %), and showed the fluorescence with a maximum emission wavelength of 450 nm at an excitation wavelength of 370 nm. Further, N, P-CQDs were employed as an efficient sensor for ultrasensitive Fe 3+ -detection at concentrations ranging from 1–20 µM and 100–300 µM, respectively. N, P-CQDs@Fe 3+ showed a high sensitivity and selectivity for AA detection. A linear response range for AA was obtained from 1 to 200 µM with limit of detection of 0.84 µM was obtained for AA. The result of MTT test showed that N, P-CQDs exhibit low toxicity, providing fast, accurate and less toxic route for testing AA in the food analysis fields.